Tutorat auprès d'apprenants en situation de handicap : quels apprentissages pour les étudiants-tuteurs d'une Grande École d'ingénieurs? - Lionel Husson; Ruth Philion; Anne Janand; Isabelle Bournaud
Educational institutions have seen a significant increase in the number of students with disabilities over the past decade. Many of these learners face challenges related to learning or academic and social integration. To help them overcome these challenges, a French Grande École of Engineering has implemented a tutoring program that consists of offering disciplinary and methodological support to learners in HS. Given the innovative nature of this project, we carried out qualitative research to understand the experience of 12 student tutors from this school who documented in an experience journal each session offered to their mentee. The analysis of the data highlights the learning achieved on the pedagogical (adaptation of their teaching and approaches), personal (contribution of a diversity of skills) and professional levels (evolution of their relationship to disability and greater openness to inclusion). Challenges were also highlighted, particularly when the skills or knowledge to be mobilized entail too great an investment, as well as the limitations of distance tutoring.